2005
DOI: 10.1097/01.wnf.0000165351.10841.fa
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine-Induced Myoclonic Status

Abstract: Olanzapine-related seizures have rarely been reported despite its proconvulsant risk. This is the first description of myoclonic status induced by this antipsychotic. A 54-year-old woman with probable Alzheimer disease developed continuous myoclonic jerks just after adding olanzapine for neuropsychiatric symptoms. She was already receiving citalopram and donepezil at low doses. Jerks coincided with spikes and polyspike/wave complexes on EEG. Olanzapine was immediately suspended and the seizures subsided. A con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 17 publications
2
12
0
4
Order By: Relevance
“…We observed that olanzapine enhances the severity of audiogenic seizures, and this effect may be explained by its serotonin 5-HT2, dopamine D2, and histamine H1 receptor antagonistic activity. Our results are in agreement with other previous reports in which olanzapine treatment was associated with seizures or lowered seizure threshold [9,94,95]. The difference observed in comparison with clozapine might be due to the dose used and higher doses might have similar effects to those observed during clozapine treatment.…”
Section: Olanzapinesupporting
confidence: 83%
“…We observed that olanzapine enhances the severity of audiogenic seizures, and this effect may be explained by its serotonin 5-HT2, dopamine D2, and histamine H1 receptor antagonistic activity. Our results are in agreement with other previous reports in which olanzapine treatment was associated with seizures or lowered seizure threshold [9,94,95]. The difference observed in comparison with clozapine might be due to the dose used and higher doses might have similar effects to those observed during clozapine treatment.…”
Section: Olanzapinesupporting
confidence: 83%
“…3,4 Because of that close temporal relationship between myoclonic jerks and haloperidol administration, a rare phenomenon of haloperidolinduced myoclonus 5 has been suggested. We consider that effect of clonazepam on supression of jerks could be negligible with these minute amounts.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Nos casos descritos na literatura ou há pobre documentação ou os pacientes estavam em uso de outras drogas, ou ainda, apresentavam doenças neurológicas associadas, o que torna difícil estabelecer a relação causal entre o uso da olanzapina e a ocorrência das crises epilépticas. (3,9,10) Em nossos casos, não havia utilização de outras drogas antipsicóticas e nem houve outros fatores etiológicos evidentes para as crises epilépticas.…”
Section: Discussionunclassified
“…Estas ocorreram em cerca de 10% dos pacientes. (3,5) Por outro lado, são raros os casos descritos de crise epiléptica induzida pelo uso da olanzapina. (2,3,10) O objetivo deste estudo é descrever e discutir dois casos de pacientes com diagnóstico de esquizofrenia e que apresentaram crises epilépticas e AE ao EEG após a introdução da olanzapina.…”
Section: Introductionunclassified